Reading images : the grammar of visual design - Kress, Gunther R.; Van Leeuwen, Theo, 1947- (London ; New York : Routledge, 2021)
"This third edition of the landmark textbook Reading Images builds on its reputation as the first systematic and comprehensive account of the grammar of visual design. Drawing on an enormous range of examples from children's drawings to textbook illustrations, photo-journalism to fine art, as well as three-dimensional forms such as sculpture and toys, the authors examine the ways in which images communicate meaning. Features of this fully updated third edition include
Includes bibliographical references and index.
ENH
Keywords: Communication in design; English language